National Resilience and Terrorism Risk Mitigation in Hajj Air Transport Services after the Kualanamu Airport Bomb Threat Incident - Agus Purwo Wicaksono; Cynthia Rahmawati (Jurnal Lemhannas RI, 2025)
Purpose: This study analyses the application of the National Resilience Concept in mitigating terrorism risks in Hajj air transport services after the Kualanamu Airport bomb threat incident. It focuses on SOP adaptability, inter-agency coordination, cyber-physical protection, regulatory responsiveness, and human-centred security culture. Study Design/Methodology/Approach: This study used a qualitative descriptive design based on documentary analysis and literature-based inquiry. Data were drawn from institutional documents, policy reports, academic publications, and reputable public records related to aviation security, terrorism risk mitigation, Hajj transport governance, airport resilience, and crisis coordination. The data were analysed through thematic coding and interpretative gap analysis. Findings: The findings indicate that the implementation of National Resilience in Hajj aviation security remains partial and uneven. The main gaps concern limited SOP adaptability, fragmented coordination and information sharing, and unresolved regulatory, technological, and human-resource challenges. These gaps may constrain preventive capability, response coordination, and recovery capacity during aviation security incidents. Originality/Value: This article contributes to aviation security and resilience studies by linking National Resilience with Hajj air transport as a high-density and high-symbolism mobility system. It highlights the need for adaptive SOP reform, integrated response coordination, stronger cyber-physical security, risk-based training, and a pilgrim-centred resilience approach.